Design and Implementation of a Local Area Network Based Multimedia Messaging Application - Benjamin Kommey; Elvis Tamakloe; Joseph Oti Boateng; Elijah Ocupualor; John Emmanuel Ayarma (Politeknik Negeri Cilacap, 2022)
Communication these days has taken a huge turn to depend extremely on the internet. Software such as WhatsApp, Facebook, Instagram, and the general social media receive about a billion active users. This demonstrates how most communication has relied on the internet. However, this approach does not serve well under some conditions. Firstly, places without internet access suffer greatly from multimedia messaging. They are either unable to initiate a conversation at all or suffer a relatively slower user experience even when they message people in close proximity. Furthermore, the cost incurred in messaging people over these platforms with people nearby could be avoided should the communication be over a local area network rather than depending on the services of an Internet Service Provider. This project investigates the design and implementation of an efficient communication system for devices near each other that relies on any local area network that a particular device is connected to. Such targeted networks include mobile Wi-Fi and cable connections. This work designed and implemented a Local Area Network based Messaging Platform, capable of working on all local networks regardless of being cable or wireless. The system is extensible, allowing for a node to re-broadcast the network onto other networks it might be connected to and works without internet access, allowing the sending and sharing of text and media files.